The English translation of Arabic preposition bi in surah Yusuf by Abdullah Yusuf Ali, and by Muhammad Taqiudin al Hilali and Muhammad Muhsin Khan - Erlya Hafidzotul Masykuroh (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2015)
ir.1/ws.c.1